The BUSINESS MODEL CANVAS STRATEGY AT OKUSA SHOP SANGATTA EAST KUTAI - Rusmiyati; Kusumawati, Nila; SP, Rahmad Bagus Ajitama (LPPM Universitas Dinamika Bangsa, 2024)
Olahan Kuliner Sangatta (OKUSA) is a shop or gallery established by LPB Pabanet (Lembaga Pengembangan Bisnis PAMA Benua Etam), as a market development effort for MSME products. The development of a Business Model Canvas (BMC) is an excellent step to assist OKUSA Stores in designing a more appropriate and effective business model. This study aims to identify and map the Business Model Canvas (BMC) at Toko OKUSA. The research method used is descriptive quantitative with data collection techniques through Focus Group Discussion (FGD), with 6 respondents consisting of 4 OKUSA administrators, namely the Chairperson, Secretary, Treasurer and Marketing Division, and 2 officials of LPB Pabanet, namely the Coordinator and 1 Staff.. This research uses SWOT Business Model Canvas analysis, SWOT Diagram and Business Model Canvas Blue Ocean Strategy. The results showed that Toko OKUSA is in a position of Stability in terms of the aspects of the Business Model analysed by Canvas in the IFAS Matrix, EFAS Matrix, and IE Matrix. Analysis with the SWOT diagram shows that Toko OKUSA is in quadrant I, which means it remains in a prime situation. Analysis of the SWOT Matrix and Blue Ocean Strategy (BOS) shows that Toko OKUSA must pay attention to the market situation and product arrangement in the gallery, utilise information media, add product value, create relationships with customers/clients on an ongoing basis. The use of technology, increasing competent human resources, product innovation and maintaining low prices. Keyword : BMC, SWOT, Blue Ocean Strategy